Boron doped Zinc Oxide for Ethanol and CO Gas Sensing - huda jabur ali (Al-Mustansiriyah Journal of Science)
This paper presents study of the properties of ZnO and ZnO:B deposited at 450oC on glass substrates by chemical spray pyrolysis (CSP) with thickness(150±5 nm) as a gas sensor for vapor ethanol and CO gases. The structure of ZnO:B  films has been found to exhibit the hexagonal wurtzite structure. The increase of boron concentration caused to decrease the grain size. The structural details were obtained from X-ray diffraction. The surface morphology of the films was studied by using the Scanning Electron Microscopy (SEM), and the Transmission electron microscopy (TEM). Sensitivity of the films is increases with the increase of boron concentration and substrate temperature